Are diabetes and blood sugar control associated with the diagnosis of eye diseases? An English prospective observational study of glaucoma, diabetic eye disease, macular degeneration and cataract diagnosis trajectories in older age - Stephen Jivraj; Caitlin Lin (BMJ Open)
Background The growing global burden of diabetes suggests a currently unrealised growth in prevalence of eye disease. This prospective observational study addresses gaps in evidence of blood sugar control as a risk factor for the diagnosis of glaucoma, diabetic eye disease, macular degeneration and cataract using waves 2–9 (2004–2019) of the English Longitudinal Study of Ageing.Methods Logistic regression modelling is used to predict the probability of self-reported diagnosis of four eye conditions separately over a 14-year period in a community-dwelling sample in England. Analysis of approximately 29 000 person observations over eight study waves from around 5600 participants for each eye disease is conducted with an average of 5.7 waves per participant. Participants’ baseline blood sugar control is categorised as non-diabetic (diabetes not previously diagnosed and glycated haemoglobin (HbA1c)<6.5), controlled (diabetes previously diagnosed and HbA1c<6.5), uncontrolled (diabetes previously diagnosed and HbA1c≥6.5) and undiagnosed (diabetes not previously diagnosed and HbA1c≥6.5). Controls at baseline for age, sex, physical activity level, body mass index and smoking status are included in the regression analysis.Results The mean age of the sample is 66 and 53% are female. The main finding from this study is that older adults in England who are controlling a diabetes diagnosis have a lower probability of developing glaucoma, diabetic eye disease or macular degeneration compared with those either without a diabetes diagnosis or with uncontrolled diabetes. Compared with those with controlled diabetes, the adjusted odds of developing glaucoma was 1.29 times higher (95% CI 1.01 to 1.65) among those not diabetic; the adjusted odds of developing diabetic eye disease was 1.20 times higher (95% CI 1.00 to 1.45) among those with uncontrolled diabetes; and the adjusted odds of developing macular degeneration was 1.38 times higher (95% CI 1.04 to 1.82) among those with undiagnosed diabetes. There was no statistically significant difference in the probability of developing cataracts by category of blood sugar control.Conclusion This study illustrates the importance of blood sugar control in the development of eye diseases and therefore supports more regular screening measures for eye disease in older age among groups at risk of diabetes.